2022
DOI: 10.1021/acsomega.2c02786
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Pyrolysis and Mild Oxidation Characteristics of Tar-Rich Coal via Thermogravimetric Experiments

Abstract: Tar-rich coal has the potential to substitute the supply of oil-gas resources, which is abundant in China. The effective conversion of tar-rich coal into oil-gas products can promote coal utilization, reduce resource wastage, alleviate environmental pollution, and benefit carbon neutrality. Nevertheless, less work, if any, has been performed on the pyrolysis and mild oxidation behaviors of tar-rich coal in Northwestern China. The influences of limited oxygen addition and an extremely low heating rate on the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Damage to oil and gas reservoirs is essentially a decrease in permeability caused by changes in the pore structure of the rock. Diagnosis and determination of damage mechanisms need to be based on core analysis, sensitivity assessment, working fluid damage simulation experiments, and field evaluation. Specific aspects, types, and processes of damage occurrence are revealed through comprehensive analysis. A large number of scholars believe that the intrusion of working fluid filtrate is the main damage factor in low permeability tight gas reservoirs. The permeability of the core matrix in such gas reservoirs is very low, and the median radius of the throat is less than 1 μm, showing high capillary force characteristics. The initial water saturation of the reservoir is often lower than the bound water saturation, leading to easy retention of the working fluid filtrate intruding into the core and difficult to flow back, which can easily lead to a significant reduction in the gas permeability and the formation of serious water-phase trap damage. When drilling in the reservoir section, the reservoir damage originates from drilling fluid leakage or filtration under the effect of positive differential pressure in the wellbore and capillary forces. Intrusion into the solid phase can cause reservoir fractures and pore throat plugging, while intrusion into the liquid phase is prone to sensitivity damage and water-phase trap damage. The depth of drilling fluid intrusion and the degree of damage increase with the increase of positive differential pressure in the wellbore and drilling time. Among them, as an important development direction of oil and gas wells, it is crucial to study the damage factors and extent of horizontal wells. Horizontal wells are an important means to increase the production capacity of oil and gas wells, but in many cases, the actual production capacity of horizontal wells cannot meet the expected plan. The main fluid-sensitive minerals in shale are clay minerals. The high content and diverse...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Damage to oil and gas reservoirs is essentially a decrease in permeability caused by changes in the pore structure of the rock. Diagnosis and determination of damage mechanisms need to be based on core analysis, sensitivity assessment, working fluid damage simulation experiments, and field evaluation. Specific aspects, types, and processes of damage occurrence are revealed through comprehensive analysis. A large number of scholars believe that the intrusion of working fluid filtrate is the main damage factor in low permeability tight gas reservoirs. The permeability of the core matrix in such gas reservoirs is very low, and the median radius of the throat is less than 1 μm, showing high capillary force characteristics. The initial water saturation of the reservoir is often lower than the bound water saturation, leading to easy retention of the working fluid filtrate intruding into the core and difficult to flow back, which can easily lead to a significant reduction in the gas permeability and the formation of serious water-phase trap damage. When drilling in the reservoir section, the reservoir damage originates from drilling fluid leakage or filtration under the effect of positive differential pressure in the wellbore and capillary forces. Intrusion into the solid phase can cause reservoir fractures and pore throat plugging, while intrusion into the liquid phase is prone to sensitivity damage and water-phase trap damage. The depth of drilling fluid intrusion and the degree of damage increase with the increase of positive differential pressure in the wellbore and drilling time. Among them, as an important development direction of oil and gas wells, it is crucial to study the damage factors and extent of horizontal wells. Horizontal wells are an important means to increase the production capacity of oil and gas wells, but in many cases, the actual production capacity of horizontal wells cannot meet the expected plan. The main fluid-sensitive minerals in shale are clay minerals. The high content and diverse...…”
Section: Introductionmentioning
confidence: 99%
“… 23 25 The initial water saturation of the reservoir is often lower than the bound water saturation, leading to easy retention of the working fluid filtrate intruding into the core and difficult to flow back, which can easily lead to a significant reduction in the gas permeability and the formation of serious water-phase trap damage. 26 30 When drilling in the reservoir section, the reservoir damage originates from drilling fluid leakage or filtration under the effect of positive differential pressure in the wellbore and capillary forces. 31 − 35 Intrusion into the solid phase can cause reservoir fractures and pore throat plugging, while intrusion into the liquid phase is prone to sensitivity damage and water-phase trap damage.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the fault underwent at least four stages of tectonic activity: the Middle Caledonian (III episode), Early Hercynian, Late Hercynian, and Indosinian periods. Although these studies have tried to determine the active stages of strike–slip faults in the cratons of the Tarim Basin, the criteria used are not uniform. , In addition, the longitudinal and planar evolution mechanisms and development patterns of strike–slip faults are relatively complex, and existing stage studies have not yet closely combined these two. Wang conducted a detailed analysis of the deformation patterns and activity of three main strike–slip faults in the study area using three-dimensional seismic small-scale slip distance strike–slip fault analysis technology, clarifying the structural style of “planar segmented connection and longitudinal layered deformation” of the strike–slip faults.…”
Section: Introductionmentioning
confidence: 99%
“…The slip distance of intra-cratonic strike–slip faults usually does not exceed several kilometers and is also known as small-scale strike-slip faults. This type of strike–slip fault is a widely developed local structure within the basin, with a complex three-dimensional geological structure. Due to its small slip distance and the limitation of seismic data resolution, the activity characteristics of this type of fault are studied. At present, there are two quantitative analysis methods for the horizontal slip distance of underground strike–slip faults: ① using 3D seismic data to deeply slice and constrain the horizontal slip distance of strike–slip faults by the distance of ancient river channels, igneous rocks, and lithofacies boundaries that have been offset and ② quantitative analysis of strike–slip fault overlapping composite structures using the conservation of area method. Based on the relevant structural types of strike–slip fault zones, it can be inferred that they were formed in a convergent or extensional tectonic background. If the main slip zone and adjacent structures are dominated by compressive structures, they are formed in a baroclinic stress environment. If the structure is mainly tensile, it is formed in a diagonal tensile stress environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation